Tactile processing in children and adolescents with obsessive-compulsive disorder - ÇANAYAZ, EMRE (TAYLOR & FRANCIS LTD, 2015)
Many obsessive-compulsive disorder (OCD) patients experience sensory phenomena, such as bodily sensations and just-right'' perceptions accompanying compulsions. We studied tactile processing in OCD by psychophysical experiments targeting the somatosensory cortex. Thirty-two children and adolescents with OCD (8 tic-related, 19 with sensory phenomena (SP)) and their sex-and age-matched controls participated in the study. After clinical assessments, two questionnaires were completed for sensory problems (Sensory Profile and Touch Inventory for Elementary-School-Aged Children). The psychophysical experiments consisted of five tasks: simple reaction time, choice reaction time, dynamic (detection) threshold, amplitude discrimination, and amplitude discrimination with single-site adaptation. The tactile stimuli were sinusoidal mechanical vibrations (frequency: 25 Hz) applied on the fingertips. Just-noticeable differences (JNDs) were found in amplitude discrimination tasks. There was no difference between the OCD group and controls in detection thresholds. However, the OCD group (especially young males) had worse amplitude discrimination (i. e., higher JNDs) than controls. Young OCD participants had reduced adaptation than young controls. Tic-related OCD participants and those with SP had higher detection thresholds than those without. Additionally, the OCD group reported more problems than controls in the Emotional/Social subset of the Sensory Profile questionnaire. The discrimination results show altered tactile processing in OCD at suprathreshold levels. This can be explained by a scaling factor modifying the sensory signal with decreasing slope at higher input levels to achieve normal Weber fractions internally. Quadratic discriminant analysis gave the best positive (76%) and negative (60%) predictive values for classifying individuals (into OCD'' or control'' groups) based on psychophysical data alone.
Keywords: Cortex; discriminant analysis; OCD; psychophysics; somatosensory; touch; SENSORY PHENOMENA; TOURETTE-SYNDROME; REPETITIVE BEHAVIORS; INHIBITION; SENSITIVITY; CHANNEL; GILLES; ABNORMALITIES; MECHANISMS; SIMULATION